Trends in breastfeeding research by Brazilian nurses - Mônica Oliveira B. Oriá; Doris F. Glick; Maria Dalva S. Alves
Exclusive breastfeeding is acknowledged as important for survival, optimal growth, and development of infants. The current review presents a synthesis of research output by Brazilian nurses on breastfeeding over the last 20 years, analyzes the theoretical and methodological issues emerging from studies on breastfeeding in Brazil, and provides directions for future research and practice by nurses in the area breastfeeding. Studies included in this review were identified through LILACS searches of Portuguese-language sources. Articles were organized and analyzed chronologically by comparing the evolution of the Brazilian Breastfeeding Program. The incomplete research output of the Brazilian nursing profession in regard to breastfeeding research needs to be addressed. In addition, specific cultural, sociological, and anthropological characteristics of Brazilian regional settings remain to be explored. Emphasis on potential confounders and critical interrelations is warranted.